Synthesis of Azide-Labeled β-Lactosylceramide Analogs Containing Different Lipid Chains as Useful Glycosphingolipid Probes - Basant Mohamed; Rajendra Rohokale; Xin Yan; Amany M. Ghanim; Nermine A. Osman; Hanan A. Abdel-Fattah; Zhongwu Guo (Molecules, 2025)
β-Lactosylceramide (β-LacCer) is not only a key intermediate in the biosynthesis of complex glycosphingolipids (GSLs) but also an important regulator of many biological processes. To facilitate the investigation of β-LacCer and other GSLs, a series of β-LacCer analogs with an azido group at the 6-C-position of the D-galactose in lactose and varied forms of the ceramide moiety were synthesized from commercially available lactose in sixteen linear steps by a versatile and diversity-oriented strategy, which engaged lipid remodeling and glycan functionalization at the final stage. These azide-labeled β-LacCer analogs are flexible and universal platforms that are suitable for further functionalization with other molecular tags via straightforward and biocompatible click chemistry, thereby paving the way for their application to various biological studies.